Cardiorespiratory evaluation in pre and post operative moments of laparoscopic cholecystectomy - Khenaifes, Tatiana Eing Granado [UNESP]; de Lima, Juliana Ferreira [UNESP]; de Camargo Pereira, Rodrigo Severo [UNESP]; Cataneo, Daniele Cristina [UNESP] (My University, 2014)
PURPOSE: To analyze the changes in both respiratory function and cardiopulmonary exercise tests results in patients subjected to laparoscopic cholecystectomy. METHODS: Fifty patients were evaluated (76% women) and the average age was 47.8±14.2 years. All individuals underwent the measurement of spirometry, manovacuometry, 6-minute walk test (6MWT) and stair-climbing test (SCT). All tests were performed at the first (PO1), fifth (PO5) and thirtieth (PO30) postoperative days. RESULTS: BMI average was 28.8±4.8 kg/m2. Sample comprised 68% non-smokers, 20% current smokers, and 12% former smokers. There was no incidence of postoperative complication whatsoever. There was a significant decrease in spirometric values at PO1, but values were similar to the ones of PRE at PO30. Manovacuometry showed alterations at PO1 displaying values that were similar to the ones of PRE at PO30. 6MWT was significantly shorter at until PO5, but at PO30 values were similar to ones of PRE. As for SCT, values were significantly compromised at PO5 and PO30 since they were similar to the ones of PRE. CONCLUSION: Patients submitted to laparoscopic cholecystectomy present a decrease in cardiorespiratory function on the first postoperative moments but there is a rapid return to preoperative conditions.
Keywords: Cholecystectomy; Exercise test; Laparoscopic; Lung Function Tests